Rates and predictors of patient-reported cognitive side effects of antiepileptic drugs: An extended follow-up. (July 2015) - Javed, Asif; Cohen, Brian; Detyniecki, Kamil; Hirsch, Lawrence J.; Legge, Alexander; Chen, Baibing; Bazil, Carl; Kato, Kenneth; Buchsbaum, Richard; Choi, Hyunmi
Highlights: In polytherapy, 11.2% with new medication had intolerable cognitive side effects. In monotherapy, 7.6% with new medication had intolerable cognitive side effects. Polytherapy and intellectual disability were predictors. Abstract: Purpose: Impact of adverse effects of antiepileptic medications (AEDs) such as cognitive side effects (CSEs) on quality of life can be significant. Here we provide an extended follow-up to our earlier study to investigate the predictors of cognitive side effects (CSEs) and relative frequency of CSEs among all commonly used AEDs. Methods: In this retrospective study, medical records of 2860 adult outpatients with epilepsy seen at our center over a 12-year period who had taken one or more AEDs were examined. Results: Of 2860 patients, 15% had intolerable CSEs attributed to at least one AED. On multiple logistic regression analysis, independent predictors of intolerable CSEs were lack of intellectual disability and polytherapy. In polytherapy, we found that intolerable CSEs were most commonly seen with topiramate (22.8% of 281 patients), significantly more than with almost all other AEDs. This was true in monotherapy as well, with significantly more intolerable CSEs occurring with topiramate (18.5% of 54 patients) than with gabapentin, carbamazepine, lamotrigine, and levetiracetam. AEDs with consistently low rates of ICSEs included gabapentin, pregabalin, lamotrigine, levetiracetam and carbamazepine. Conclusion: These data can help facilitate selection of AEDs.